Penerapan Metode Six Sigma Dengan Konsep DMAIC Sebagai Alat Pengendalian Kualitas Produk - Sarifa Tuasamu; Jusuf Sahupala; Tina. D Kaisupy (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the value of sigma before improvement is carried out and find out the causes of defects in the production process, as well as produce proposals for improvement and quality control of products. The population in this study was Arsel furniture table products during April 2015 to March 2016 which amounted to 420 products. Sampling using purposive sampling techniques and with the considerations used, the number of samples used was 306 samples. The results of research using the Six Sigma method with the DMAIC concept as a product quality control tool in Arsel Mebel found defective products in the form of rupture during cutting, removal of laminate materials, size errors, and the process of drilling table legs. The results of the analysis showed that the defective product that was more dominant was broken at the time of cutting, which was 38 percent.